The Relationship Between Corporate Governance Mechanisms and Financial Performance of Non-Financial Firms in Pakistan - Dr. Usman Ali; Afzal Ahmad; Dr. Abdul Hafeez; Dr. Tariq Jameel; Dr. Muhammad Saeed Ahmad; Akhtar Mehmood (Social Science Review Archives, 2025)
The primary objective of this study is to investigate the relationship between corporate governance practices and the financial performance of non-financial firms listed on the Pakistan Stock Exchange (PSX). Corporate governance was assessed by utilizing Principal Component Analysis (PCA) to create a single governance score, which was based on eleven distinct indicators, each reflecting different aspects of governance structures. Financial performance was similarly measured using PCA, incorporating four key financial indicators to provide a comprehensive assessment of the firms' financial health. The research relied on secondary data obtained from the annual financial reports of non-financial firms listed on the PSX, spanning a period of twelve years, from 2013 to 2024. Panel data analysis techniques were applied for the empirical investigation. The results reveal a statistically significant and positive relationship between corporate governance and financial performance. Anchored in established corporate governance theories, the study highlights how governance frameworks can impact a firm's financial results. The findings contribute to the expanding literature on the governance-performance link and offer valuable insights for future research and policy development, especially within Pakistan’s non-financial sector.